Stimulating Science Process Skills through the ‘Puffer Fish’ Game for Children Aged 5–6 Years - Maulida, Anissa Choirum; Sundari, Rista (THUFULA, 2025)
Abstract: This study aims to determine how the "pufferfish" game stimulates the science skills of children aged 5-6 years through simple experimental activities. This game involves a reaction between vinegar and baking soda that produces gas that makes the balloon inflate to resemble a pufferfish. This study is a descriptive qualitative study with data collection techniques in the form of observation, interviews, and documentation. The results show that this game has a positive impact on children's science process skills, such as the ability to observe, ask questions, try, and draw simple conclusions. Despite some technical obstacles, this activity still provides a fun and meaningful learning experience. The role of teachers is very important in accompanying children during the experimental process. Thus, the "pufferfish" game can be used as an alternative science activity that is appropriate for the developmental stage of early childhood. Keywords: Games, Child, Experiments, and Science